If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-3c + -4) + -1(2c + -4) = 0 Reorder the terms: 3(-4 + -3c) + -1(2c + -4) = 0 (-4 * 3 + -3c * 3) + -1(2c + -4) = 0 (-12 + -9c) + -1(2c + -4) = 0 Reorder the terms: -12 + -9c + -1(-4 + 2c) = 0 -12 + -9c + (-4 * -1 + 2c * -1) = 0 -12 + -9c + (4 + -2c) = 0 Reorder the terms: -12 + 4 + -9c + -2c = 0 Combine like terms: -12 + 4 = -8 -8 + -9c + -2c = 0 Combine like terms: -9c + -2c = -11c -8 + -11c = 0 Solving -8 + -11c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -11c = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -11c = 0 + 8 -11c = 0 + 8 Combine like terms: 0 + 8 = 8 -11c = 8 Divide each side by '-11'. c = -0.7272727273 Simplifying c = -0.7272727273
| 9c-16=20 | | 7x-27=45+11x | | 325=6+7 | | 2a+6+4a+13= | | x^2+x-6=9-x | | 3x^(3/4)=-24 | | 2t^2-7t-5=0 | | 27/S=9 | | -X^2-11x-25=0 | | 4+3=7y-21 | | 1.5a=1.6a+5 | | 22-3x=-8 | | 2=t/-14 | | 1.25x=8 | | 4r=3(r-2) | | 94=8j+30 | | y=4(x+6)-7 | | x-5/9=8/9 | | 5+4x+5+48= | | -3(t-4)+9t=8t-6 | | 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x |